Effects of central obesity on maternal complications in Korean women of reproductive age. Issue 2 (March 2019) - Lim, Jisun; Han, Kyungdo; Kim, Suk Young; Cho, Young Hye; Yoon, Yeong Sook; Park, Hye Soon; Yoo, Soon Jib; Kim, Kyoung Kon
Abstract: Background: Considering the obesity-related complications in pregnancy and during delivery, prepregnancy central obesity may also affect pregnancy-related complications. This study aimed to assess the relationship between prepregnancy central obesity and adverse maternal outcomes in Korean women, by using the Korean National Health Insurance Service (NHIS) cohort. Methods: In this population-based retrospective cohort study, we used data from the NHIS database, which contains information of health-care utilisation, diagnosis and prescription, and mortality for almost the whole Korean population, together with data from the NHIS health checkup database from 2005 to 2015. The NHIS health checkup data (645−280 days before childbirth) of mothers who had deliveries (total, 783, 406 deliveries) from 2006 to 2015 were collected. For maternal adverse outcome data, we searched for diagnoses of maternal complications made during the period of 280 days before each delivery. The odds for maternal complications according to 8 body mass index (BMI) and 10 waist circumference (WC) categories were analysed using logistic regression. Results: The incidence rates of eclampsia/preeclampsia, caesarean section, multiple gestation, and polycystic ovary syndrome (PCOS) increased according to the increase of BMI and WC. In contrast, the incidence rate of premature rupture of membrane (PROM) was inversely correlated with BMI and WC. In the low BMI (<17.5 and 17.5–19.9 kg/m 2 ) and low WC (<60 and 60.0–64.0 cm) groups, the odds of threatened abortion were elevated. Conclusion: Prepregnancy WC was closely linked to some maternal complications, including eclampsia/preeclampsia, cesarean section, PCOS, and PROM, in a manner similar to prepregnancy BMI.